2016
DOI: 10.1007/s00167-016-4359-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management of medial meniscus posterior horn root tears is associated with worsening arthritis and poor clinical outcome at 5-year follow-up

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
209
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(230 citation statements)
references
References 36 publications
7
209
0
1
Order By: Relevance
“…Individuals with accelerated KOA have substantially greater pain and disability when compared to their peers without accelerated KOA, and this becomes evident prior to radiographic onset of the disease . Accelerated KOA may be a unique subset of KOA characterized by specific pathologic features (e.g., meniscal root tears ) that could differentiate it from typical KOA; however, this hypothesis has not been specifically examined. If specific pathologic profiles could be used to differentiate people at risk for accelerated KOA, it may help identify adults with early‐stage accelerated KOA or those at high risk for accelerated KOA, and thereby inspire novel prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with accelerated KOA have substantially greater pain and disability when compared to their peers without accelerated KOA, and this becomes evident prior to radiographic onset of the disease . Accelerated KOA may be a unique subset of KOA characterized by specific pathologic features (e.g., meniscal root tears ) that could differentiate it from typical KOA; however, this hypothesis has not been specifically examined. If specific pathologic profiles could be used to differentiate people at risk for accelerated KOA, it may help identify adults with early‐stage accelerated KOA or those at high risk for accelerated KOA, and thereby inspire novel prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…If left untreated, meniscal extrusion can occur rendering the meniscus nonfunctional resulting in degenerative arthritis of the knee. 3,4 Chung et al 5 compared the outcomes of 37 patients with meniscal root repairs with 20 patients who underwent partial meniscectomies. The repair group had superior subjective knee rating and knee function scores with less radiographic progression of arthritis.…”
mentioning
confidence: 99%
“…Along with the overall difference in arthritic changes, 35% of the patients who had undergone a meniscectomy to treat a meniscal root tear underwent conversion to total knee arthroplasty (TKA) by 5-year follow-up, whereas none of the patients who had undergone a meniscal root repair underwent conversion to TKA 38. To further support the importance of recognising and repairing meniscal root tears, Krych et al 39 reported poor clinical outcomes, worsening of OA and a 31% conversion to arthroplasty in 52 patients treated conservatively for posterior root tears at a mean follow-up of 5 years.…”
Section: Strategies and Evidencementioning
confidence: 99%
“…Moreover, studies have indicated that indirect costs associated with TKA can grow to as much as US$68 000 per patient, increasing the economic burden on the patient and the overall healthcare infrastructure. In this regard, Krych et al reported that the 16 patients (31%) with untreated meniscal root tears that underwent conversion to TKA by 5-year follow-up resulted in a US$1.1 million direct cost to society 39. Although TKA is a cost-effective treatment when compared with non-operative management for end-stage OA, treating medial meniscal root tears conservatively or with meniscectomy will likely accelerate the rise in the projected volume of TKA cases, putting further strain on the US healthcare system due to the increased costs.…”
Section: Strategies and Evidencementioning
confidence: 99%